Computer-based selection tests: psychological and measurement implications of adaptive testing - Alkhadher, Othman (1994)
The aim of this thesis is to develop realistic expectations about the psychological and psychometric implications of using computerized adaptive tests (CAT). A review is carried out of literature on computerized-based testing (CBT) and CAT. A field study as well as four laboratory experiments were conducted to achieve that goal The current research strongly suggested the equivalence between the paper-and-pencil (P&P) and CAT formats for the Abstract Reasoning (AR) and Mechanical Reasoning (MR) tests of the Differential Aptitude Tests (DAT), but failed to do so for the Numerical Ability (NA) test. Also, the CAT version of OAT can predict a performance variable as accurately as can the P&P format. Overall testees' attitudes toward several aspects of computerized testing were positive. The results confirmed the negative relationship between computer experience and computer anxiety. Moreover, knowledge of CAT behaviour negatively affected subjects' performance, but did not increase the level of their state anxiety. This suggested that a form of feedback acts during the adaptive test which has a negative effect on testees' performance and response time. This assumption was confirmed. Subjects spend a shorter time on the subsequent item after negative feedback (wrong) on the previous item than after positive feedback (right). It has been found that although the response time for answering an individual item was higher for CAT format than for P&P format, the CAT version of DAT resulted in a 20% reduction in completion time of the test. Also, the difficulty level of the initial items has a significant effect on testees' overall scores. The findings of this thesis suggest that CAT has numerous advantages and potential for improving the efficiency and accuracy of testing, and has potential areas of future contribution within personnel selection and assessment. This potential can be realized if proper consideration is made in designing, developing, and implementing these testing systems, and if professional standards are maintained by developers and users.